PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI BOWLING KAMPUS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA N 3 TAMBUSAI UTARA PADA MATERI LIMIT FUNGSI - Yani, Juhri; Afri, Lusi Eka; -, Arcat (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This study examines the effect of cooperative learning with campuses bowling strategy to grade students learning outcomes. The population in this study a class XI student of SMAN 3 Tambusai Utara. The sampling technique was done by simple random sampling. Samples XI2 class as experimental class and class XI1 as a control class. With the test  of  normality  and  homogeneity  tests  showed  the  two  samples  were  normally  distributed  and  homogeneous. Analysis of data using U test with = 0.05 showed Ucount = 90.5 and Utable = 98, Ucount > Utable so H0 was accepted. So it  was concluded that  there was significant cooperative  learning model with campus bowling strategy on the results of students mathematics learning.